Endometrioid carcinoma arising from the remnant ovarian tissue - Paulose, Manjuraj Kuzhiyamattathil; Parambil, Noushiba Valiya; Kutty, Sathiamma Puthuvilayil; Salahuddin, Sameer; Khalam, Muneer Abdul; Jacob, Sheela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Endometrioid carcinoma of ovary is a subtype of epithelial tumours of the ovary. It can be distinguished from serous and mucinous tumours by presence of tubular glands resembling that of malignant endometrium. Traditionally, Ovarian carcinoma treatment involves the combination of cytoreductive surgery and platinum-based chemotherapy. Fortunately, because of a better overall understanding of ovarian tumorigenesis and advancements in the disease’s epigenetic and molecular profiling, a paradigm shift has emerged with the identification of new disease biomarkers and the proposal of targeted therapeutic approaches to postpone disease recurrence and decrease side effects, while increasing patients’ survival. It is usually associated with poor prognosis due to late clinical presentation allied with the common acquisition of chemo resistance and a high rate of tumour recurrence. The chemotherapy backbone for patients with high-grade advanced epithelial ovarian cancer (HG-AOC) is carboplatin and paclitaxel followed by a maintenance therapy either with bevacizumab, with a PARP inhibitor, or with a combination of both, which is defined by the presence of a Homologous Recombination Deficiency (HRD) and by the BRCA1/2 status (This case showed a negative HRD and BRCA1/BRCA2 mutation status). Hence effective screening, accurate diagnosis and personalised multidisciplinary treatments are crucial for improving patient’s survival and quality of life. We report a case of endometrioid carcinoma of ovary arising from the remnant ovarian tissue in a 53year old women who underwent TAH+BSO done 12 years back for a benign cause and aims to summarize molecular studies involved in endometroid ovarian carcinoma pathogenesis as potential therapeutic targets.